Event-Triggered-Based External Consensus Protocol of RBF-ARX-Model-Based Networked Multiagent Systems with Nonlinear Dynamics and Communication Delays - Qi Lei; Ying Luo (Discrete Dynamics in Nature and Society)
An event-triggered-based external consensus control protocol with delay compensation for networked multiagent systems (NMASs) with nonlinear dynamics and network-induced delays is discussed in this paper. An RBF-ARX modelling method is adopted to approximate a nonlinear system. By utilizing the RBF-ARX model, the locally linearized time series model can be obtained to describe the behaviour of agents with nonlinear characteristics. An event-triggered control protocol with communication delay compensation is proposed to reduce the effects of network-induced delays and the times of the agent’s control update and communication between others by applying the idea of a prediction strategy. The event-triggered mechanism for each agent only depends on the deviation between its own output and the delay-compensated output of neighboring agents. Then, a distributed event-triggered-based and delay-compensated external consensus control protocol is given. Under this proposed control protocol, both the consensus and stability of the system can be proved. Finally, a numerical simulation is performed to verify the availability of our results.